A redefinition of Pseudokellya Pelseneer, 1903 (Bivalvia: Cyamiidae) and the description of a new species from the Southern Ocean - Zelaya, Diego Gabriel; Ituarte, Cristian Federico
A new species of Pseudokellya, Pseudokellya franki from South Shetland Islands, is described. P. franki is characterized by its subcircular shell outline, the periostracum forming low lamellate commarginal folds, radial sculpture absent, and by the presence of a single posterior siphonal opening, a fact that is in contrast with that reported for the type species of Pseudokellya, Kellia cardiformis Smith, 1885. The presence of a complete follicle surrounding each developing oocyte, persisting throughout vitellogenesis, a condition not currently known for other bivalves, is confirmed as a generic diagnostic character. The generic redefinition, based on shell morphology and anatomical features described for Pseudokellya franki, is given. Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología Invertebrados; Argentina Fil: Ituarte, Cristian Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina